Fulfillment of Maintenance for Trader's Wife Kroya Cilacap Market After Fire Perspective of Wahbah Al-Zuhaili - Wilan Prahadika Aura Nisa; Abd. Rouf (Muwafaqat: Journal of Islamic Law, 2025)
The fire that occurred in Kroya Market, Cilacap, significantly impacted traders, particularly regarding the fulfillment of financial support within families. In Islam, the husband is responsible for providing for his wife and children, as emphasized by Wahbah al-Zuhaili in Fiqh Islam wa Adillatuhu, which outlines the scope of nafkah (financial support). This study aims to describe the fulfillment of husbands’ financial support for their wives—traders at Kroya Market—after the fire, through Wahbah al-Zuhaili’s perspective.This empirical juridical study uses a qualitative approach with data gathered through interviews, observation, and documentation. Primary data came from informant interviews, while secondary sources included literature studies.The findings show that overall fulfillment of financial support for wives decreased due to the fire. Out of the five aspects of nafkah, only food, housing, and household furnishings were adequately fulfilled in line with Wahbah al-Zuhaili’s views. Although the provision of domestic help was unmet, it remains justifiable in light of financial constraints. Clothing provision showed inconsistencies. Despite these challenges, husbands continued striving to fulfill obligations according to their capacity.